Crystallization Process as a Final Part of Zero Liquid Discharge System for Treatment of East Baghdad Oilfield Produced Water - Salih, Miqat Hasan; Al-Alawy, Ahmed Faiq (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
This study investigated the application of the crystallization process for oilfield produced water from the East Baghdad oilfield affiliated to the Midland Oil Company (Iraq). Zero liquid discharge system (ZLD) consists of several parts such as oil skimming, coagulation/flocculation, forward osmosis, and crystallization, the crystallization process is a final part of a zero liquid discharge system. The laboratory-scale simple evaporation system was used to evaluate the performance of the crystallization process. In this work, sodium chloride solution and East Baghdad oilfield produced water were used as a feed solution with a concentration of 177 and 220 g/l. The impact of temperature (70, 80, and 90 °C), mixing speed (300, 400, and 500 rpm), feed concentration (177 and 220 g/l), and time (0.5-9.5 h) on the crystallization performance for oilfield produced water treatment were investigated on evaporation rate and recovery. The recovery increased with increasing temperature and mixing speed while decreasing with an increase in feed concentration. Pure water and salts were recovered from the concentrated produced water, the recovery of pure water at 80 °C, 400 rpm, and 220 g/l feed concentration was 82.22 and 81.35% after 5.5 h for NaCl solution (i.e., simulated oilfield produced water) and oilfield produced water, respectively.